A Case Report: The Effect of Thread Embedding Acupuncture on Partly-Controlled Asthma - Yusuf Gunawan; Irma Nareswari (Faculty of Medicine, University of Jember, 2021)
Asthma is a chronic inflammatory disorder of the respiratory tract where many cells and cellular elements play a role, especially eosinophils, IgE, and other components. Uncontrolled asthma causes the quality of the patient's life to decline. Acupuncture is one of the complementary therapies that are scientifically proven to help cure asthma. Many studies have proven that acupuncture plays a role in the anti-inflammatory process. In this case report, we used the acupuncture method of thread embedding penetration from point EX-B1 to BL13, LI11, ST36, and BL23 on both sides. Acupuncture therapy is done once when the patient first arrives. The results after 3 months observations showed that patients experienced an improvement in eosinophil count, decreased level of IgE, and increased Asthma Control Test values. The improvement showed patients were fully controlled in the first month until the end of the evaluation. Therefore, thread embedding could be a good, safe, and effective treatment for asthma in adults.Keywords: asthma, thread embedding acupuncture, anti-inflammation